Thermostability of Bacillus cereus Penicillinase - Williams, Daniel H. (1966)
Williams, Daniel H., III (Hahnemann Medical College, Philadelphia, Pa.), A. Bondi, A. G. Moat, and F. Ahmad. Thermostability of Bacillus cereus penicillinase. J. Bacteriol. 91:257–261. 1966.—The extracellular penicillinase of Bacillus cereus, strain 13-10, exhibited an unusual thermostability. Whereas it was completely and irreversibly inactivated by heating at 70 C, it retained considerable activity when heated at 100 C for 30 min. The active enzyme remaining was completely stable to further heating at temperatures from 40 to 100 C for as long as 1 hr. Preparations of the enzyme heated to 100 C possessed pH (7.0) and temperature (37 C) optima identical with the unheated enzyme. Furthermore, both enzyme preparations exhibited identical combining capacity for the substrate (penicillin G), suggesting that the two preparations had similar hydrolytic properties. Our findings suggest that heating of penicillinase at 100 C results in the formation of a protein complex which is resistant to further denaturation by heat and other agents. Addition of certain metal ions to the enzyme solution before heat treatment increased the stability to heat at 100 C by virtue of their ability to induce complex formation. Pectin was shown to decrease thermostability, presumably by preventing aggregation of proteins present in the enzyme preparations. The well-known stabilizing effect of gelatin may be attributed to its role in enhancing complex formation.